2015
DOI: 10.1038/ijo.2015.155
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the associations between fat-free mass, resting metabolic rate and energy intake in the context of total energy balance

Abstract: 1 2 Background:The relationship between body composition, energy expenditure and ad libitum 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
98
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 46 publications
14
98
1
Order By: Relevance
“…In support of this proposal, a number of studies have demonstrated that resting metabolic rate (but again, not fat mass) is a determinant of within-day eating behavior (70,75,76). For example, Caudwell et al (75) demonstrated in overweight and obese individuals that resting metabolic rate (but not fat mass) was a determinant of daily hunger, self-selected meal size and daily energy intake under conditions of high and low energy density.…”
Section: Body Composition Energy Expenditure and Food Intakementioning
confidence: 83%
See 2 more Smart Citations
“…In support of this proposal, a number of studies have demonstrated that resting metabolic rate (but again, not fat mass) is a determinant of within-day eating behavior (70,75,76). For example, Caudwell et al (75) demonstrated in overweight and obese individuals that resting metabolic rate (but not fat mass) was a determinant of daily hunger, self-selected meal size and daily energy intake under conditions of high and low energy density.…”
Section: Body Composition Energy Expenditure and Food Intakementioning
confidence: 83%
“…However, while protein-energy relationships are thought to be critical for survival time during under nutrition (61-63), few have considered energy expenditure, or its determinants such as body composition, as major sources of feedback in the control of dayto-day food intake (64,65). Recently, a number of studies have sought to re-examined the specific roles that fat mass, fat-free mass and energy expenditure play in the control of food intake, and in contrast to the prevailing regulation, these studies suggest fat-free mass has a stronger influence on day-to-day food intake than fat mass (66)(67)(68)(69)(70)(71). For example, Blundell et al (68) reported that fat-free mass was positively associated with self-selected meal sized and total daily energy intake in 93 overweight and obese individuals.…”
Section: Body Composition Energy Expenditure and Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, by applying various statistical models to data on body composition, EE and energy intake (including a mediation model using path analysis approaches), a number of recent studies have shown that the impact of FFM on food intake is not direct, but rather indirect since FFM influences daily hunger, self-selected meals size and daily energy intake via its effect on resting EE. 4,6,10 It has been proposed by Hopkins and Blundell 11 that such FFM-induced energy requirements represent 'a physiological source of hunger that drives food intake at a level proportional to basal energy requirements', and that 'this longterm (tonic) signal of energy requirements would help 'tune' energy intake to EE, and help ensure the maintenance and execution of key biological and behavioral processes'.…”
Section: Passive Role Of Ffm In Driving Energy Intakementioning
confidence: 99%
“…It was estimated that about 300,000 people die each year from obesity and related causes, which puts this disorder as the second leading cause of death. In fact, being both overweight and obese increases the risk of several diseases and health conditions such as high triglycerides, cholesterol, diabetes, heart disease, high blood pressure, tumors (breast, colon, and endometrial), sleep disorders, and respiratory problems [7][8][9].…”
Section: Introductionmentioning
confidence: 99%